Study of clinical profile of meconium aspiration syndrome in relation to gestational age and birth weight and their immediate outcome at Narayana Medical College Hospital, Nellore, India - Gangu Dhilli, Ravindra Nath; A., Penchalaiah (International Journal of Contemporary Pediatrics, 2017)
Background: Meconium staining of the amniotic fluid occurs in approximately 13% of live births; this percentage increases with increasing gestational age at delivery. MAS occurs in approximately 5% of infants born through MSAF. This study was undertaken to understand the factors causing MAS and clinical profile of meconium aspiration syndrome in relation to gestational age and birth weight and their immediate outcome. Methods: The present study is a prospective study of 58 neonates admitted to NICU fulfilling the criteria of MAS were included in the study over a period of 2 years. The babies who were born with meconium stained liquor, suctioning was done by the obstetricians first at the delivery of shoulder and then handed over to pediatrician and depending upon whether the meconium is present below the vocal cords or not and whether baby is vigorous or not, endotracheal intubation and bag and tube ventilation was given. The babies with clinical features MAS were admitted to NICU and were observed for their immediate outcome in the hospital. Results: During the study period, out of 4994 deliveries, 882 (17.6%) babies had meconium stained liquor and out of these 882 babies, 58 (6.5%) babies had MAS. Out of 426 cases of respiratory distress admitted to NICU, 58 (13.6%) cases diagnosed of MAS. MAS occurred most commonly in babies having fetal distress and in mothers with history of PIH. It is seen more commonly in babies born through caesarean section and in term babies with mean gestational age of 38-40 weeks of gestation and mean birth weight of 2.68 Kg. It was most commonly associated with babies who were depressed at birth and most common cause of mortality was due to birth asphyxia contributing 37.5% of cases of MAS. Conclusions: MAS is an entity which is commonly seen in term and post term babies with birth weight >2.5 Kg.